The effect of supplementary irrigation on yield and water use efficiency of Stevia (Stevia rebaudiana Bertoni) in greenhouse and farm investigation - Houshang Ghamarnia; Zahra Jalili; Farhang Sargordi (فناوری‌های پیشرفته در بهره‌وری آب, 2022)
Iran, with a mean precipitation of 230 mm per year, is classified as arid and semi-arid region in the world, facing a water crisis. Since, water resources with high quality for irrigation are limited, therefore the use of supplement irrigation as a method for reducing water consumption is essential in the future. Stevia is a plant with medicinal and anti-diabetic effects, native to the mountainous region of Amoeba, located on the border of Brazil and Paraguay, which is widely cultivated in Shiraz and Isfahan of Iran. The diterpene glycosides in this plant (the main cause of the very sweet taste in plant extracts) are up to 300 times sweeter than sugar used in the pharmaceutical and food industries. In present study, effect of Supplementary irrigation (without Supplementary irrigation, one Supplementary irrigation in flowering and tow Supplementary irrigation in flowering and seeding) were carried out on (Stevia Rebaudiana B.) during two-year period (2017-2018) in greenhouse and research farm. The results showed that supplementary irrigation to prevent reduced sugar yield in the greenhouse and research farm environment was about (18.7, 18.1) and (20.7 and 21.4) irrigation in the first and second year of cultivation, respectively. The result showed that plant tolerance to supplementary irrigation to non- supplement irrigation to avoid reducing sugar yield in greenhouse conditions were obtained as: (18.7 and 18.1), (20.7 and 21.4). According to those results, irrigation of stevia with two supplementary irrigations at the time of flowering and seeding was recommended to increase plant yield.